Family matters: Ranking within fund families and fund inflows - Alexander Kempf; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2007)
This paper examines the influence of the position of a fund within its family on its subsequent net-inflows. Our empirical study of the US equity mutual fund market shows that reaching a top position within the family leads to large inflows. These inflows accrue beyond those expected, given the performance of the fund in its respective market segment. The effect is much stronger in large families than in small families. We also find that inflows significantly increase if a fund moves into the top positions within its family from one year to another. These results lead to competition within the fund family and to important risk taking incentives for fund managers.
Keywords: G23; 330; Mutual Funds; Fund Families; Performance Flow Relationship